Diseño e implementación de un sistema de telecomunicaciones para la vigilancia de UAV´S de nueva generación. - Carrasco Sampedro, Isaac Moisés (2024)
The main objective of this research study was to focus on a telecommunication system for the surveillance of new generation UAVs will be designed and implemented for a frequency assigned for the global use of Automatic Dependent Surveillance-Broadcast (ADS-B). The main objective of the project is to design a surveillance system that allows the detection and tracking of UAVs in real time. Due to the advancement and commercialization of UAVs, there are new technologies that help us and facilitate the surveillance of UAVs. For the selection of hardware and software an analysis of the options available in the market is made to select the most compatible option with the scope of the project which will begin structuring the selection process of hardware and software with the evaluation of requirements and ending with the final selection. The system selection will be compared on the devices that exist in the market and will consider evaluating the frequency of operation in relation to the system's transmission and reception requirements, etc. Once the transmitter and receiver parameters are selected, it is necessary to analyze the antenna, taking into account parameters such as center frequency and antenna gain. The decoding software was selected according to its working model, Currently FlightAware, has the ability to receive the signal transmitted from the new generation UAVs, the position data is displayed on the interface through FlightAware and PiAware software, and to recognize the position of the received UAVs hoping to have the ability to detect and track multiple UAVs simultaneously. Analyze how the different receiving parameters are decoded within the FlightAware software. At the end the results are performed to demonstrate the feasibility of the proposal presented.